The long-term effects of German unification on wages, employment and growth: a trigger for a shift to a new market constellation - Heike Joebges; Rudolf Zwiener; Nora Albu (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
Hajo Riese introduced the concept of market constellations to analyse the changing macroeconomic effects of German monetary policy from the 1950s to the 1980s, when monetary policy, focused on internal and external price stability in Germany, enabled continued net export surpluses. Yet changing external conditions supported economic growth only in the 1950s and 1960s, leading to stagflation in the 1980s. Related to approaches based on Riese's concept for more recent decades, the paper argues that the policy response to German unification costs – including labour-market reforms aimed at regaining lost cost competitiveness and reducing high unemployment – triggered a new market constellation, lasting from the mid 1990s until the 2007–2008 global financial crisis. In the context of the European Economic and Monetary Union, this compressed effective demand and supported stagnation, leading overall to negative effects on employment and growth.
Keywords: 330; Hajo Riese; market constellation; monetary policy; German exports; cost competitiveness; German unification; labour market reforms; Hartz reforms; unit labour costs; REER; wage-led demand regime; macroeconomic policy regimeF16; J30–32